Picinguaba pitanga: A NEW GENUS AND SPECIES OF CRICKET FROM THE STRAND VEGETATION OF SOUTHEASTERN BRAZIL (ORTHOPTERA: GRYLLOIDEA: ENEOPTERIDAE) - Mello, F. A.G. (REVISTA DE AGRICULTURA, 2015)
Picinguaba pitanga: A NEW GENUS AND SPECIES OF CRICKET FROM THE STRAND VEGETATION OF SOUTHEASTERN BRAZIL (ORTHOPTERA: GRYLLOIDEA: ENEOPTERIDAE)